Two years eight months and twenty-eight nights : a novel - Rushdie, Salman (New York : Random House, 2015)
"From Salman Rushdie, one of the great writers of our time, comes a spellbinding novel that blends history, mythology, and a timeless love story. A lush modern fairytale in which our world has been plunged into an age of unreason, Two Years Eight Months and Twenty-Eight Nights is a breathtaking achievement and an enduring testament to the power of storytelling"--
"Once upon a time, in a world just like ours, there came "the time of the strangenesses." Reason receded and the loudest, most illiberal voices reigned. A simple gardener began to levitate, and a powerful djinn -- also known as the Princess of Fairyland -- raised an army composed entirely of her semi-magical great-great-great-grandchildren. A baby was born with the ability to see corruption in the faces of others. The ghosts of two philosophers, long dead, began arguing once more. And a battle for the kingdom of Fairyland was waged throughout our world for 1,001 nights -- or, to be more precise, for two years, eight months, and twenty-eight nights. Two Years, Eight Months and Twenty-Eight Nights is a masterful, playfully enchanting meditation on the power of love and the importance of rationality, replete with flying carpets and dynastic intrigue"--
Keywords: Jinn -- Fiction; Magic -- Fiction; FICTION / Literary; FICTION / Fairy Tales, Folk Tales, Legends & Mythology; Fantasy fiction; Love stories